The Development of Training Course for Teaching Activities to Promote Critical Thinking Skills for Thai Language Teachers in Primary Schools under Teacher Training Experiences Network Schools in Suratthani Province - พันธ์น้อย, วิชุนี (Ratchaphruek Journal, 2019)
The research on “The Development of Training Course for Teaching Activities to Promote Critical Thinking Skills for Thai Language Teachers in Primary Schools under Teacher Training Experiences Network Schools in Suratthani Province” used research methodology in 4 steps are step 1: Needs analysis and needs for curriculum development.; interviewed principles and 20 Thai language teachers in primary level and bring synthesized information to design the structure and elements of the training curriculum. Step 2: Design and develop training course by curriculum and teaching professional; assessment and evaluation, Thai language, and check the suitability. Step 3: Experiment with samplings; there are 30 Thai language teachers in primary schools under Teacher Training Experiences Network Schools in Suratthani Province which gained them by Purposive sampling method. And separated into 2 periods .Period 1, training by the course in 3 days, 18 hours. There are 5 units; Unit 1 Activity experiences for primary school students, Unit 2 Introduction of Critical Thinking Skills, Unit 3 Teaching Activities to Promote Critical Thinking Skills, Unit 4 Assessment and Evaluation to Promote Critical Thinking Skills, Unit 5 Writing plan for Teaching Activities in Thai Language teaching. Period 2, apply the knowledge gained from the training course to write a teaching plan and teaching experimental for 2 weeks, present the plan and results of teaching activities, and reflect individual development results. Step 4: Course Evaluation, evaluation of satisfaction on Thai language teachers who attended the training course. The data analysis was used statistics as following; average, mean, standard deviation, and t-test. The results are 1) Needs analysis and needs for curriculum development found that the principles and Thai language teachers in primary schools had the same opinions that the training course should be developed to promote teaching instruction, techniques and teaching methods to Thai language teachers. Moreover, it should focus on the measurement and evaluation to match the contents and ages. In consideration of meet the needs for development, contents type and designing, media and assessment and evaluation. 2) Develop training course consist of principles and rationale, objectives, contents, training method, media and resources, assessment and evaluation. 3) The experimental results of the training course for teaching activities to promote critical thinking skills found that their knowledge after training was higher than before attending the course statistically significant at the .05 level. 4) Ability to write activity plans to promote critical thinking skills was at a high level, average at 2.82 criteria. 5) The ability to organize learning activities to promote critical thinking skills was at a high level, average 2.82 criteria. 6) Satisfaction of Thai language teachers on the training course to promote critical thinking skills was at the highest level, 4.64 criteria.